2001
DOI: 10.1103/physrevlett.87.146602
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Acoustoelectric Effect inLa0.67Ca0.33MnO3Films

Abstract: We have studied acoustoelectric (AE) effect produced by surface acoustic waves (SAW) in a monolithic layered structure, composed of piezodielectric We show that the anomalous effect is caused by strong modulation of the film conductivity produced by the SAW elastic deformations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…In this paper, the magnetocaloric eect was studied in the La 0.8 Sr 0.2 MnO 3 thin lm deposited on the yz-cut LiNbO 3 single crystal substrate. The La 0.8 Sr 0.2 MnO 3 compound was chosen for his reasonably high magnetocaloric eect [7,8] and for our previous experience in growing high quality La-based lms [9].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, the magnetocaloric eect was studied in the La 0.8 Sr 0.2 MnO 3 thin lm deposited on the yz-cut LiNbO 3 single crystal substrate. The La 0.8 Sr 0.2 MnO 3 compound was chosen for his reasonably high magnetocaloric eect [7,8] and for our previous experience in growing high quality La-based lms [9].…”
Section: Introductionmentioning
confidence: 99%
“…The electronphonon interaction becomes mediated not only by the ordinary deformation potential but also by the piezoelectric ͑for acoustic phonons͒ or Fröhlich ͑for optical phonons͒ mechanisms associated with the polarization field. Recently, Ilisavskii et al 5 reported differences in acoustoelectric properties induced by a reversal in propagation direction of elastic modes in La 0.67 Ca 0.33 MnO 3 layers on LiNbO 3 , which were attributed to an interference between the deformation and piezoelectric mechanisms. In zinc blende semiconductors, the interference between the deformation potential and the Fröhlich interactions induced by a LO mode propagating along the zϭ͓001͔ direction leads to different Raman polarizabilities along the xЈϭ͓110͔ and yЈϭ͓1 10͔ axes.…”
mentioning
confidence: 99%
“…Eq. (3) is valid for our range of parameters because the product ω c τ is less than one for τ = 5×10 -14 s and the magnetic field of our experiment [18]. The electron spin is not included in Eq.…”
mentioning
confidence: 95%
“…(1) [18]. Correspondingly, the current at non-zero magnetic field normalized to its value at zero field has the form (…”
mentioning
confidence: 99%